PRODUKSI BIOGAS DARI LIMBAH PENGOLAHAN KELAPA SAWIT DENGAN PROSES FERMENTASI PADAT - R Sudradjat; Erra Y; Umi K; Evi K (Jurnal Penelitian Hasil Hutan, 2003)
The aim of this investigation was to evaluate the characteristic of biogas produced from the wastes of palm-oil solid fermentation processing, the assessment on its potential prospect was also studied. The wastes consist of the mixture of empty bunches, pericarp, and sludge. The mixing ratio in weight was 1.3: 1.2: 1.0 respectively. The conditions implemented in the fermentation process were temperature (55° C), and content of dry matters or substrate (i.e. mixture of empty bunches, pericarp, and sludge) in the fermentation digester (35 %). The fermentation was conducted either in batch or continuous system. The weight ratios between substrate and inoculum were consecutively 25 : 500, 50 : 500, 75 : 500, and 100 : 500.Results revealed that fermentation in the batch system at 25 : 500 ratio as such afforded biogas with the highest yield (145 ml per liter-hour) and the most intense degradation on the organic matters (32.3 % VS). meanwhile, the fermentation using continuous system at 25 : 500 brought out biogas with the highest production (1623.7 ml per liter-d). Keywords : Palm oil processing, wastes, fermentation, substrate, and inoculum.